Plan de mejoramiento en el área de tesorería de la empresa de transporte Cootranschinchiná ubicada en el municipio de Chinchiná-Caldas (2014)
The transport sector is characterized by strong competition, now in addition to appropriate vehicles for the service and the need to comply with the standards required in Colombia, it is necessary to establish companies that allow providing a higher quality of service to those who are part of it. The cooperative Chinchiná conveyor is dedicated to land transport of passengers carried in the industry for the last 40 years and has 211 members, it belongs to the solidarity sector and is monitored by the ministry of transport. The company has three areas: transportation, quality management, and treasury office, this last one being a strategic area of the company. For this reason we decided to make an improvement plan to bring more competitiveness to the company and that the area can meet its organizational objectives; several visits to the treasury area were conducted in order to find its shortcomings. There was found mainly internal customer dissatisfaction because their payments and requirements are often delay, due to not standardized processes, poor communication in the area and undefined work plans. Given that most of the income of Cootranschinchiná is perceived by partners there is a need to improve the area in order to improve the response to internal customers. With the improvement plan in the area of treasury, Cooperative transporters Chinchiná seeks to provide the area necessary tools for effective service delivery and have the necessary means for the proper execution of work, in addition to well structured company that allows greater competitiveness and leadership in the sector.